Análise econômica probabilística do confinamento de novilhos com diferentes pesos iniciais - Olegário, Janaine leal (2017)
The objective of this study was to analyze the finishing steers economical viability fed in a high-concentrate diet on different starting weights (240, 270, 300, 330, 360 and 390 kg) using probabilistic Monte Carlo simulation methods. Diet was formulated with the following ingredients: whole grain corn and protein core. For the simulation of the financial indicator Net Present Value (NPV), the cash flows were calculated considering historical prices between 2003 to 2015, for each starting weight, the purchase of the animals occurred in May,and the sale occurred when they reached their slaughter weight. Simulations were performed to obtain the following analyzes:Probability distribution types determination of all cost itemsusing spearman correlation between random input variables, risk analysis, stochastic dominance type, sensitivity analysis using zootechnical indicators and revenue. Economic viability maintained the best return on investment for the initial weight 390 kg. The Net Present Value was R$ -253.80,R$ -253.80, R$ 4.74, R$ -20.17, R$ -32.23, and R$ 31.04, and the probability of a higher Net Present Value or Equal to zero was 13.8%, 10.80%, 52.90%, 47.90%, 45.90%, and 59.40% respectively. The use of the stochastic dominance type determined that the pairs of accumulated distribution curves in some cases dominated the larger ones. But in the case of the accumulated curves to starting weight 390 kg, these ones dominated all the others.It was possible to identify two types of investor: First and second order stochastic dominance.The investor of the project with starting weights 240 and 270 kg was characterized as first-order dominance and the others as second-order dominance. The sensitivity analysis showed that the most influential items in the financial indicator were fat animalsale, leananimal purchase, and concentrate cost. The use of feedlot with very light initial weight represented an investment alternative with high risk and low economic return.